Mehrmotorenantriebssysteme - Intelligente Betriebsstrategie - Brückner, Uwe; Strop, Malte; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Methods for the simulation of the pressure, stress, and temperature distribution in the contact of fractal generated rough surfaces - Magyar, Balázs; Sauer, Bernd (Proceedings of the Institution of Mechanical Engineers, Part J: Journal of Engineering Tribology)
In this paper, the influence of surface roughness on the local tribological load with a dry sliding contact is studied. First, three artificial rough surfaces with similar structure but different asperity heights are generated and projected on a smooth ball. After that, a contact pattern is determined between a rough ball and a smooth surface taking into account the elastic only as well as the linear elastic-perfectly plastic material description. On the basis of the calculated contact pressure distribution, the subsurface stresses and a three-dimensional temperature distribution in the sliding contact are calculated. The solutions show that a low surface roughness not necessarily results in low local tribological load of the surface.

Multi-Ebenen-Simulation zur Berechnung der lokalen Lebensdauer in hochbelasteten Wälzkontakten - Kiekbusch, T; Magyar, Balázs; Sauer, B (VDI Berichte 2308)

Oberflächenanalyse der Tribokontakte von Radialwellendichtsystemen - Emrich, S; Burkhart, C; Magyar, Balázs; Kopnarski, M; Sauer, B

Parametrisches thermisches Netzwerk zur Simulation der Temperaturverteilung eines RWDR-Prüfstandes - Heimes, J; Bactavatchalou , R; Bock, E; Frölich, D; Kaiser, F; Langner, T; Morgenstern, S; Magyar, B; Sauer, B

Reproduzierbarkeit der Maßhaltigkeit im Fused Deposition Modeling - Knoop, F.; Lieneke, Tobias; Schöppner, Volker (Rapid Tech - International Trade Show & Conference for Additive Manufacturing)
Fused Deposition Modeling (FDM) is used for prototypes, single-partproduction and small batch productions of thermoplastic components. This manufacturing technique has the huge benefit that no forming tool is needed. The knowledge about dimensional deviations which occur in the FDM process is necessary for calculating fits and for determining tolerances. A major challenge is the reproducibility of the dimensional accuracy of FDM parts and the reproducibility between different FDM machines. There are many influential factors on the dimensional accuracy in the FDM process for example geometric, material-specific or process-specific factors, which are considered in this paper. The influence of the part position on the build platform of a Stratasys Fortus 400mc is analyzed in terms of the achievable dimensional accuracy. For this purpose, the temperature distribution in the actively heated build chamber is investigated and possible correlations to the dimensional accuracy are identified. The reproducibility of one machine is examined by a multiple production of the test specimens. In addition, a comparison with three other FDM machines from Stratasys is made. Afterwards, the long-term reproducibility of the dimensional accuracy is verified to consider how environmental influences such as maintenance or modification of machine components affect the dimensional accuracy of the FDM process.

TEHD Simulation von Radialwellendichtringen - Thielen, S; Magyar, Balázs; Sauer, B

Verträglichkeitsuntersuchungen am tribologischen Ersatzsystem - Thielen, S; Magyar, Balázs; Burkhart, C; Sauer, B

Additive Manufacturing of a Lightweight Rotor for a Permanent Magnet Synchronous Machine - Lammers, Stefan; Adam, Guido; Schmid, Hans-Joachim; Mrozek, Rafael; Oberacker, Rainer; Hoffmann, Michael; Quattrone, Francesco; Ponick, Bernd (EDPC 2016)
Additive Manufacturing (AM), also known as 3D printing, is a relatively new technology which enables the toolless production of components and entire assemblies directly from a CAD file. Today, the technology is still not widely used in industrial production. It is mainly limited to special applications, although it shows great potential. In this paper, first approaches are shown to apply AM to the production of rotors for permanent magnet synchronous machines (PMSM). The possibilities of a lightweight design with a low moment of inertia as well as the influence on the magnetic anisotropy for an improved sensorless control of PMSM are pointed out. The results clearly demonstrate the great potential of additive manufacturing in electrical engineering applications.

Beitrag zur Reduzierung der Verluste von fluidabdichtenden Wellendichtsystemen - Nolte, Karsten

Dimensional accuracy of polymer laser sintered parts: Influences and measures - Josupeit, Stefan; Delfs, Patrick; Lieneke, Tobias; Adam, Guido; Gessler, Monika; Pfisterer, H.; Schmid, Hans-Joachim (Rapid Tech - International Trade Show & Conference for Additive Manufacturing)
In the polymer laser sinter process, part quality depends on many influencing factors along the process chain. For application of the technology in series production and an integration of laser sintered parts into a technical environment, the dimensional accuracy of parts has to be taken into account. Therefore, occuring deviatons and their scattering have to be reduced and homogenized based on process parameters and build job layout. In this work, the dimensional accuracy of laser sintered parts is analyzed for varied parameter values. Influences of different process and geometrical build job parameters on dimensional deviatons are figured out. The experimental results allow an evaluation of more and less important influences. Finally, measures are deduced to reduce and homogenize dimensional deviations.

Dimensional tolerances for additive manufacturing: Experimental investigation for Fused Deposition Modeling - Lieneke, Tobias; Denzer, Vera; Adam, Guido; Zimmer, Detmar (CAT 2016)
Additive manufacturing creates parts in layers without using formative tools. Compared to established manufacturing processes, additive manufacturing offers many advantages. However, only a few research institutions and technology-leading companies use additive manufacturing for end-use part production because relevant challenges have not been sufficiently researched yet. Missing restrictions become apparent in the available geometrical accuracy. The objective of this investigation was the experimental determination of dimensional tolerances using standard parameters. To this end, a methodical procedure was set up. Based on experimentally determined deviations, dimensional tolerances were derived.

Dimensional tolerances for additive manufacturing: Experimental investigation of manufacturing accuracy for selective laser melting - Lieneke, Tobias; de Groot, Stefan; Adam, Guido; Zimmer, Detmar (ASPE 2016 Summer Topical Meeting)

Effizienzorientierte Optimierung der Baustruktur von MMDS-Sammelgetrieben - Brückner, Uwe; Strop, Malte; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

EHD Simulation eines Kettengelenks - Magyar, Balázs; Thielen, S; Löwenstein, M; Becker, A; Sauer, B

Functional investigation of zero lead radial shaft seal counter-surfaces turned with a special method - Thielen, S; Magyar, Balázs; Sauer, B; Schneider, F; Mayer, P; Kirsch, B; Müller, R; v. Harbou, E; Aurich, J.C.

Funktionsintegration additiv gefertigter Dämpfungsstrukturen bei Biegeschwingungen - Künneke, Thomas; Zimmer, Detmar (DVM Tagung - Additiv gefertigte Bauteile und Strukturen)
Additive manufacturing processes offer great freedom in the design of components. This enables a high level of function integration. Also in terms of vibration damping, additive manufacturing yields opportunities for the selective implementation of damping functions due to their characteristics. In powder-based processes the disperse support material can be kept inside the cavities of the structure. This powder material can act as a particle damper. Due to the freedoms in design, the damping behavior can be adjusted selectively by varying the geometrical features of the cavities. Within this paper, investigations on the damping behavior of additive manufactured parts regarding free bending vibrations are focused.

Gekoppelte thermische und tribologische Analyse von Schneckengetrieben - Oehler, M; Magyar, Balázs; Sauer, B

Geometrische Genauigkeit von Lasersinter-Bauteilen: Einflüsse und Maßnahmen / Dimensional accuracy of polymer laser sintered parts: Influences and measures
In the polymer laser sinter process, part quality depends on many influencing factors along the process chain. For application of the technology in series production and an integration of laser sintered parts into a technical environment, the dimensional accuracy of parts has to be taken into account. Therefore, occurring deviations of the process have to be known to define tolerances for part design. Dimensional deviations and their scattering have to be reduced and homogenized based on process parameters and build job layout. In this work, the dimensional accuracy of laser sintered parts is analyzed for varied parameter values. Influences of different process and geometrical build job parameters on dimensional deviations are figured out. The experimental results allow an evaluation of more and less important influences. Finally, measures are deduced to reduce and homogenize dimensional deviations.

Influences on the dimensional Accuracy of Laser Sintered Parts along the Process Chain - Josupeit, Stefan; Delfs, Patrick; Lieneke, Tobias; Schmid, Hans-Joachim (27th Annual International Solid Freeform Fabrication Symposium)

Intelligent Operating Strategy for an Internal Rubber Mixer's Multi-Motor Drive System Based on Artificial Neural Network - Strop, Malte; Zimmer, Detmar (IEEE 21st International Conference on Emerging Technologies and Factory Automation (ETFA))

Machbarkeitsstudie 3D Druck Elektromotoren - Lammers, Stefan; Quattrone, Francesco; Mrozek, Rafael

Optimierung von Planetengetriebemotoren - Einfluss des Übersetzungsverhältnisses auf das Kosten-, Gewichts-, Verlust-, Dynamik- und Zuverlässigkeitsverhalten von Planetengetriebemotoren - Kücükyavuz, Ali Kemal

Örtlich konzentrierte Mehrmotorenantriebssysteme - Ein Lösungsansatz für ganzheitlich modulare Antriebssysteme - Brückner, Uwe; Strop, Malte; Zimmer, Detmar (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)

Reconstruction of three-dimensional turned shaft surfaces with fractal functions - Thielen, Stefan; Magyar, Balázs; Piros, Attila (Tribology International)
A method for the reconstruction of turned shaft surfaces with a (fractal) Weierstrass–Mandelbrot-function (WMF) is presented. The WMF is modified to allow to freely choose a phase-shift for every frequency. The reconstruction is based on distinct profiles in axial and tangential direction and the statistical distribution of low-wavelength portions of the surface is taken into account by adding t-distributed random deviations to the surface. The work is validated by reconstructing measured shaft surfaces with different manufacturing parameters, which shows good accuracy for periodic surfaces. This method allows for a characterization of surfaces with a limited number of parameters and can be used to store the characteristics of measured surfaces with a reduced amount of data compared to a point-cloud surface.
Keywords: Roughness; Structure; Fractal; Machining

Reproducibility of the Dimensional Accuracy - Investigations for FDM - Knoop, Frederick; Lieneke, Tobias; Schoeppner, Volker (ASPE Spring Topical Meeting)

Reproducibility of the Dimensional Accuracy - Investigations for FDM - Knoop, Frederick; Lieneke, Tobias; Schoeppner, Volker (Summer Topical Meeting 2016)

Verbundprojekt Energieeffiziente Federkraftbremse: Abschlussbericht. Berichtszeitraum: 01.05.2012 - 31.03.2016 - Schadomsky, Magnus Hubert; Zimmer, Detmar; Kriegel, Nils-Peter; Neumann, Christoph; Küter, Winfried; Menzel, Eckard

Calculation of the efficiency of worm gear drives - Magyar, Balázs; Sauer, B (Power Transmission Engineering)

Ein Beitrag zur modellbasierten Entwicklung magnetorheologischer Bremsen - Wiehe, Ansgar

Entwicklung einer Methode zur systematischen Erarbeitung von Maßtoleranzen für additive Fertigungsverfahren - Lieneke, Tobias; Adam, Guido; Leuders, Stefan; Knoop, Frederick; Josupeit, Stefan; Delfs, Patrick; Funke, Nils; Zimmer, Detmar (Proceedings of the Rapid Tech 2015)

Entwicklung einer Methode zur systematischen Erarbeitung von Maßtoleranzen für additive Fertigungsverfahren - Lieneke, Tobias (Rapid Tech 2015)

Intelligente Betriebsstrategien für Mehrmotorenantriebssysteme - Hölscher, Christian; Strop, Malte; Zimmer, Detmar (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Investigation of wear resistance of dry and cryogenic turned metastable austenitic steel shafts and dry turned and ground carburized steel shafts in the radial shaft seal ring system - Frölich, D.; Magyar, Balázs; Sauer, B.; Mayer, P.; Kirsch, B.; Aurich, J.C.; Skorupski, R.; Smaga, M.; Beck, T.; Eifler, D. (Wear)
The state of the art industrial manufacturing process to produce shafts as counter surfaces for radial shaft seal rings is plunge grinding. This process consists of three major steps. The blank is turned to a slight diameter-oversize followed by the heat treatment and the hard-finishing by plunge grinding. The geometric surface structures of the resulting shafts in general exhibit a stochastic distribution. These surface characteristics contribute to a reliable and stable sealing functionality. And the surface and subsurface hardness generally leads to a higher wear resistance of the shaft. Motivated by economic benefits and in order to achieve a compact production process for at least ten years, turning is investigated as an alternative manufacturing process. However due to the resulting lead structure on the shaft surface and the associated risk of leakage it has not become prevalent yet. In this paper turned shafts of the metastable austenitic steel AISI 347 (1.4550, X6CrNiNb1810) are investigated as alternative material for counter surfaces of radial shaft seal rings and compared to turned shafts of carburized AISI 5115 (1.7131, 16MnCr5). In addition to surfaces dry turned at room-temperature, cryogenic turned AISI 347 counter surfaces are analyzed. By applying cryogenic cooling, the formation of deformation-induced α′-martensite in the surface layer is possible during the turning process. Endurance tests in radial shaft seal ring test rigs are performed and complemented with detailed investigations of microstructure, micro-hardness and surface topography. The results are compared to results of state of the art ground AISI 5115 shafts.
Keywords: Radial shaft seal ring; Shaft surface; Cryogenic turning; Metastable austenitic steel; Deformation-induced martensite formation

On design for Additive Manufacturing - evaluating geometrical limitations - dell'Aere, Guido; Zimmer, Detmar (Rapid Prototyping Journal)
Purpose – The purpose of this paper is to present Design Rules for additive manufacturing and a method for their development. Design/methodology/approach – First, a process-independent method for the development of Design Rules was worked out. Therefore, geometrical standard elements and attributes that characterize the elements’ shapes have been defined. Next, the standard elements have been manufactured with different attribute values with Laser Sintering, Laser Melting and Fused Deposition Modeling, and their geometrical quality was examined. From the results, Design Rules for additive manufacturing were derived and summarized in a catalogue. Findings – Due to the process independent method, Design Rules were developed that apply for the different considered additive manufacturing technologies equally. These Design Rules are completely function-independent and easily transferable to individual part designs. Research limitations/implications – The developed Design Rules can only apply for the considered boundary conditions. To extend the Design Rules’ validity, their applicability should be proven for other boundary conditions. Practical implications – The developed Design Rules practically support the design of technical parts. Additionally they can be used for training and teaching in the field of “design for additive manufacturing”. Originality/value – The developed Design Rules constitute a first step toward general Design Rules for Additive Manufacturing. Thus, they might form a suitable basis for further scientific approaches, and the Design Rules can be used to set up teaching documentations for lessons and seminars.

On tolerances for additive manufacturing - Adam, Guido (Inside 3D Printing Conference and Expo)

Systematical determination of dimensional tolerances for additive manufacturing - Lieneke, Tobias (26th Annual International Solid Freeform Fabrication Symposium)

Systematical determination of tolerances for additive manufacturing by measuring linear dimensions - Lieneke, Tobias; Adam, Guido; Leuders, Stefan; Knoop, Frederick; Josupeit, Stefan; Delfs, Patrick; Funke, Nils; Zimmer, Detmar (26th Annual International Solid Freeform Fabrication Symposium)
Additive manufacturing offers many technical and economical benefits. In order to profit from these benefits, it is necessary to consider the manufacturing limits and restrictions. This applies in particular to the geometrical accuracy. Therefore, the achievable geometrical accuracy needs to be investigated, which enables the determination of realistic tolerances. Thus, two different aims are considered. The first aim is the determination of dimensional tolerances that can be stated if additive manufacturing is used under normal workshop conditions. Within the second aim, relevant process parameters and manufacturing influences will be optimized in order to reduce dimensional deviations. To achieve both aims a method was developed first. This method identifies relevant influential factors on the geometrical accuracy for the processes Fused Deposition Modeling (FDM), Laser Sintering (LS) and Laser Melting (LM). Factors were selected that are expected to affect the geometrical accuracy mainly. The first investigations deal with measuring linear dimensions on a designed test specimen and the derivation of achievable dimensional tolerances. This paper will present both, the developed method and the first results of the experimental investigations.

Systematische Erarbeitung von Konstruktionsregeln für die additiven Fertigungsverfahren Lasersintern, Laserschmelzen und Fused Deposition Modeling - Adam, Guido

Wellendichtsysteme - Zimmer, Detmar; Nolte, Karsten; Hütte, Jürgen

Wellendichtsysteme - Zimmer, Detmar; Nolte, Karsten; Hütte, Jürgen

Worm Gear Drives with High Efficiency - Oehler, M; Magyar, Balázs; Sauer, B (VDI-Berichte 2255)

A comprehensive model of wear, friction and contact temperature in radial shaft seals - Frölich, D.; Magyar, Balázs; Sauer, B. (Wear)
Radial shaft seals are used in a variety of applications, where rotating shafts in steady housings have to be sealed. Typical examples are crankshafts, camshafts, differential gear or hydraulic pumps. In the operating state the elastomeric seal ring and the shaft are separated by a lubrication film of just a few micrometers. Due to shear strain and fluid friction the contact area is subject to a higher temperature than the rest of the seal ring. The stiffness of the elastomeric material is intensely influenced by this temperature and thus contact pressure, friction and wear also strongly depend on the contact temperature. In order to simulate the contact behavior of elastomer seal rings it is essential to use a comprehensive approach which takes into consideration the interaction of temperature, friction and wear. Based on this idea a macroscopic simulation model has been developed at the MEGT. It combines a finite element approach for the simulation of contact pressure at different wear states, a semi-analytical approach for the calculation of contact temperature and an empirical approach for the calculation of friction. In this paper the model setup is presented, as well as simulation and experimental results.
Keywords: Radial shaft seal ring; Contact temperature; Wear; Friction torque; Finite element simulation

Application of Self-optimizing Systems - Hölscher, Christian; Keßler, Jan Henning; Meyer, Tobias; Rasche, Christoph; Reinold, Peter; Sextro, Walter

Auswahl anwendungsoptimaler Antriebssysteme als Basis für die Komposition von Antriebsbaukästen - Klause, Alexander; Zimmer, Detmar (Entwerfen - Entwickeln - Erleben 2014. Beiträge zur virtuellen Produktentwicklung und Konstruktionstechnik)

Calculation of the efficiency of worm gear drives - Magyar, Balázs; Sauer, B

Data Acquisition and Signal Analysis from Measured Motor Currents for Defect Detection in Electromechanical Drive Systems - Lessmeier, Christian; Enge-Rosenblatt, Olaf; Bayer, Christian; Zimmer, Detmar (European Conference of the PHM Society 2014 (EPHM14))

Design for Additive Manufacturing - Element transitions and aggregated structures - Adam, Guido; Zimmer, Detmar (CIRP Journal of Manufacturing Science and Technology)
Additive Manufacturing technologies create parts layer by layer. Thereby, lots of benefits are offered. Especially extended design freedoms provide new potentials for the design of technical parts. To make these benefits accessible to different user groups, design rules for Additive Manufacturing were developed within the project ‘‘Direct Manufacturing Design Rules’’. Therefore a process independent method was defined first. Next, design rules were developed for Laser Sintering, Laser Melting and Fused Deposition Modeling. The results were summarized in a design rule catalog and support a suitable design for Additive Manufacturing

Erweiterung des Gültigkeitsbereichs von Konstruktionsregeln beim Lasersintern - Adam, Guido

Extension of prior developed design rules (LS) - Adam, Guido; Zimmer, Detmar (ASPE - Spring topical meeting 2014)

Extension of prior developed design rules for laser sintering - Adam, Guido

intelligent Drive Module (iDM) - Hölscher, Christian; Zimmer, Detmar

Intelligent Operating Strategies for Multi-Motor Drive Systems - Strop, Malte; Hölscher, Christian; Zimmer, Detmar (OPT-i 2014. 1st International Conference on Engineering and Applied Sciences Optimization)

Intelligente Betriebsstrategien für Mehrmotorenantriebssysteme - Zimmer, Detmar; Hölscher, Christian; Strop, Malte (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Konzeption von Antriebssystembaukästen auf der Basis von branchenspezifischen Antriebslösungen - Klause, Alexander; Zimmer, Detmar (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Numerical Investigation of the Contact of Rough Surfaces - Magyar, Balázs; Sauer, B

On the fatigue properties of metals manufactured by selective laser melting – The role of ductility - Leuders, Stefan; Lieneke, Tobias; Lammers, Stefan; Tröster, Thomas; Niendorf, Thomas (Journal of Materials Research)
Abstract

Semi-Analytical Model for the Contact Temperature Calculation in Radial Shaft Seals - Frölich, D; Magyar, Balázs; Sauer, B

Simulation der Hysteresereibung von Elastomeren - Magyar, Balázs; Sauer, B

Systematic investigations of minimum feature sizes and geometrical accuracies - Adam, Guido; Zimmer, Detmar

Theoretical Analysis of the Local Load Distribution of Rough Surfaces - Magyar, Balázs; Sauer, B

Tribologische Untersuchung eines neuen Werkzeughalters zur Polierbearbeitung von keramischen Fliesen - Sousa, F.J.P.; Glawe, M; Magyar, Balázs

AutASS - Autonome Antriebstechnik durch Sensorfusion für die intelligente, simulationsbasierte Überwachung & Steuerung von Produktionsanlagen“ Teilvorhaben: „Beanspruchungs- und Lastkollektivbestimmung“ - Lessmeier, Christian; Kürpick, Markus; Zimmer, Detmar

Beitrag zur Geräuschminderung an Federkraftbremsen - Wecker, Markus

Contact Modeling of Rough Surfaces - Magyar, Balázs; Sauer, B

Design for additive manufacturing - Adam, Guido; Zimmer, Detmar

Die Potentiale additiver Fertigung nutzen - Adam, Guido

Energetische Optimierung eines Mehrmotorenantriebssystems für Kautschukinnenmischer - Hölscher, Christian; Michaelis, Stefanie; Strop, Malte; Zimmer, Detmar

Konstruktionsregeln für additive Fertigungsverfahren - Adam, Guido; Zimmer, Detmar (Konstruktion)
Additive Fertigungsverfahren stellen Bauteile und Baugruppen aus Kunststoff- oder Metallwerkstoffen schicht¬weise, ohne formgebendes Werkzeug her. Daraus resultierende Gestaltungsmöglichkeiten schaffen einen großen Nutzen für Anwender dieser Technologie. Um diesen Nutzen einem breiten An-wenderkreis zugänglich zu machen, werden im Projekt „Direct Manufacturing Design Rules“ (DMDR) Konstruktionsregeln für Additive Fertigungsverfahren erarbeitet. Hierzu wird zunächst eine verfahrens-unabhängige Methode zur Erarbeitung der Konstruktionsregeln entwickelt. Diese ermöglicht die Erar-beitung von Konstruktionsregeln, die zunächst für die hier betrachteten Additiven Fertigungsverfahren und Werkstoffe gelten. Die Ergebnisse werden in einem Konstruktionsregelkatalog zusammengefasst.

Konstruktionsregeln für additive Fertigungsverfahren - Ausbildung, Lehre - Adam, Guido

Multiobjective Optimization including Safety of Operation Applied to a Linear Drive System - Meyer, Tobias; Hölscher, Christian; Menke, Michael; Sextro, Walter; Zimmer, Detmar (PAMM - Proceedings in Applied Mathematics and Mechanics)

Ökonomisch-ökologische Bewertung von elektromechanischen Antriebssystemkonzepten. Ein Werkzeug zur schnellen und wirtschaftlichen Konzipierung optimaler Antriebssysteme für spezifische Anwendungen - Zimmer, Detmar; Klause, Alexander (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Situationsbezogene Luftspaltoptimierung am Linearmotor eines schienengebundenen Fahrzeugs - Schmidt, Alexander

Temperaturberechnung im RWDR-Dichtkontakt - Magyar, Balázs; Frölich, D; Sauer, B

Tribo-Dynamical Analysis of Cylindrical Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P (VDI Berichte 2199)

Anforderungen an Bremssysteme der industriellen Antriebstechnik - Kriegel, Nils-Peter; Zimmer, Detmar (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Anforderungen an Bremssysteme in der industriellen Antriebstechnik - Kriegel, Nils-Peter; Wecker, Markus; Zimmer, Detmar (VDI-Konferenz Innovative Bremstechnik)

Elektromechanische Antriebe - Zimmer, Detmar

Elementbasierte Erarbeitung von Konstruktionsregeln für additive Fertigung - Adam, Guido; Zimmer, Detmar

Entwicklung eines modularen Antriebssystems für Kautschukinnenmischer - Fiekens, Nicolas; Zimmer, Detmar; Michaelis, Stefanie; Schöppner, Volker; Hallmann, Tobias (DKT 2012. Deutsche Kautschuk Tagung)

Hierarchical optimization of coupled self-optimizing systems - Hölscher, Christian; Zimmer, Detmar; Keßler, Jan Henning; Kruger, Martin; Trächtler, Ansgar (IEEE International Conference on Industrial Informatics)

Kontaktmodellierung von technisch rauen Oberflächen - Magyar, Balázs; Sauer, B

Low friction Rotary Shaft Seal. Verlustleistungsreduziertes Dichtsystem - Nolte, Karsten; Zimmer, Detmar (International Sealing Conference)

Simulation and Experimental Analysis of Mixed Lubrication of K Type Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P

Tribo-dynamische Untersuchungen von Zylinderschneckengetrieben - Magyar, Balázs

Tribological Investigation of K Type Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P (Acta Polytechnica Hungarica)

Untersuchung von Bauteilschäden elektrischer Antriebsstränge im Belastungsprüfstand mittels Statorstromanalyse - Zimmer, Detmar; Lessmeier, Christian; Hameyer, Kay; Piantsop Mbo'o, Christelle; Coenen, Isabel (ant Journal - Anwendungsnahe Forschung für Antriebstechnik im Maschinenbau)

Untersuchung von Bauteilschäden elektrischer Antriebsstränge im Belastungsprüfstand mittels Statorstromanalyse - Lessmeier, Christian; Piantsop Mbo'o, Christelle; Coenen, Isabel; Zimmer, Detmar; Hameyer, Kay

Bestimmung der Biegesteifigkeit eines Schubgliederbandes - Zimmer, Detmar; Möller, Jens (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Component-Based Hazard Analysis for Mechatronic Systems - Priesterjahn, Claudia; Sondermann-Wölke, Christoph; Tichy, Matthias; Hölscher, Christian (14th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

Direct Manufacturing Design Rules - Adam, Guido; Zimmer, Detmar

DMDR Direct Manufacturing Design Rules. Erarbeiten von applikationsunabhängigen Konstruktionsregeln - Zimmer, Detmar; Adam, Guido (Rapid.Tech 2011 Fachmesse und Anwendertagung für Rapid-Technologie)

Dynamiksimulation von im Mischreibungsgebiet arbeitenden Schneckengetrieben - Magyar, Balázs; Sauer, B; Horák, P (VDI-Berichte 2155)

Experimentelle Untersuchungen zur Ermittlung der Schwingungsdämpfung von Zylinderschneckengetrieben - Magyar, Balázs; Fábián, Cs.; Sauer, B (VDI-Berichte 2164)

Hybrid Planning for Self-Optimization in Railbound Mechatronic Systems - Adelt, Philipp; Esau, Natascha; Hölscher, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Zimmer, Detmar

Steigerung der Anlagenverfügbarkeit von Antriebssystemen durch methodische und modulare Konzeption. Modulare Konzeption von als Einzelstücke oder in Kleinserien hergestellten Antriebssystemen mit großer Nennleistung - Fiekens, Nicolas; Zimmer, Detmar (VDI/VDE-Tagung mit Fachausstellung Antriebssysteme 2011. Elektrik, Mechanik und Hydraulik in der Anwendung)

Experimentelle Untersuchung der Zahnreibungszahl von Schneckengetrieben mit der Flankenform K - Magyar, Balázs; Horák, P; Sauer, B; Fábián, Cs (GÉP)

Investigation of the Lubrication of ZI Type Worm Gear Drives - Magyar, Balázs; Horák, P

Konstruktionsregeln für additive Fertigung in Lehre und Forschung - Adam, Guido; Zimmer, Detmar (Newsletter Berliner Kreis)

Numerical and Experimental Analysis of TEHD Lubrication of ZK Type Worm Gear Drives - Magyar, Balázs; Horák, P (VDI-Berichte 2108)